Inhabited television: broadcasting interaction from within collaborative virtual environments - Benford, Steve; Greenhalgh, Chris; Craven, Mike; Walker, Graham; Regan, Tim; Morphett, Jason; Wyver, John (ACM Transactions on Computer-Human Interaction (TOCHI) - Special issue on human-computer interaction and collaborative virtual environments TOCHI, 2000)
Inhabited television combines collaborative virtual environments (CVEs) with broadcast television so that on-line audiences can participate in television shows within shared virtual worlds. We describe a series of experiments with inhabited television, beginning with the NOWninety6 poetry performance, The Mirror, and Heaven & Hell—Live. These early experiments raised fundamental questions for inhabited television concerning the extent to which it is possible to establish fast-paced social interaction within a CVE, and to which it is possible to produce a coherent and engaging broadcast of this action. We then present a fourth more recent experiment, Out of This World, that directly addressed these questions. We describe how the formulation of inhabited television design principles, combined with the use of dedicated production software for scripting and directing a show and for controlling virtual cameras, enabled us to create a fast-moving and more coherent experience.